The Signal Transduction Protein PII Controls Ammonium, Nitrate and Urea Uptake in Cyanobacteria - Watzer, Björn; Spät, Philipp; Neumann, Niels; Koch, Moritz; Sobotka, Roman; Macek, Boris; Hennrich, Oliver; Forchhammer, Karl (Frontiers in Microbiology, 2019)
PII signal transduction proteins are widely spread among all domains of life where they regulate a multitude of carbon and nitrogen metabolism related processes. Non-diazotrophic cyanobacteria can utilize a high variety of organic and inorganic nitrogen sources. In recent years, several physiological studies indicated an involvement of the cyanobacterial PII protein in regulation of ammonium, nitrate/nitrite and cyanate uptake. However, direct interaction of PII has not been demonstrated so far. In this study, we used biochemical, molecular genetic and physiological approaches to demonstrate that PII regulates all relevant nitrogen uptake systems in Synechocystis sp. strain PCC 6803: PII controls ammonium uptake by interacting with the Amt1 ammonium permease, probably similar to the known regulation of E. coli ammonium permease AmtB by the PII homologue GlnK. We could further clarify that PII mediates the ammonium- and dark-induced inhibition of nitrate uptake by interacting with the NrtC and NrtD subunits of the nitrate/nitrite transporter NrtABCD. We further identified the ABC-type urea transporter UrtABCDE as novel PII target. PII interacts with the UrtE subunit without involving the standard interaction surface of PII interactions. The deregulation of urea uptake in a PII deletion mutant causes ammonium excretion when urea is provided as nitrogen source. Furthermore, the urea hydrolyzing urease enzyme complex appears to be coupled to urea uptake. Overall, this study underlines the great importance of the PII signal transduction protein in the regulation of nitrogen utilization in cyanobacteria.